(untitled) (International relations and international law Journal, 2016)
Europe is one of the most signiﬁcant directions of Kazakhstan’s foreign policy. For Kazakhstan the need and perspective to develop relations with the European Union is deﬁned by the role and place of this alliance in European and world politics, economy and culture. The European Union and Kazakhstan are the partners, and they conduct a permanently enlarging consistent dialogue. The European Union and Kazakhstan have the common interests in the spheres of regional and international security, economy, social and cultural development as well as in the realization of investment operations and international projects, and attraction of cutting-edge technologies and knowledge to the country. Maintenance of relations between our republic and the European Union at a high level is a priority. There are several stages in the development of cooperation between Kazakhstan and the EU. The contemporary period, that we are witnessing, is aimed at the strengthening and expanding the EU’s position in Central Asia and the Caspian region. Today the EU has already worked out its own vision on the future of Central Asia as a region that could become a barrier to drug trafﬁcking, illegal migration and religious extremism.